2022
DOI: 10.1111/1471-0528.17132
|View full text |Cite
|
Sign up to set email alerts
|

Clinical‐pathological features in placentas of pregnancies with SARS‐CoV‐2 infection and adverse outcome: case series with and without congenital transmission

Abstract: Objective To correlate clinical outcomes to pathology in SARS‐CoV‐2 infected placentas in stillborn and live‐born infants presenting with fetal distress. Design Retrospective, observational. Setting Nationwide. Population Five stillborn and nine live‐born infants from 13 pregnant women infected with SARS‐CoV‐2 seeking care at seven different maternity units in Sweden. Methods Clinical ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 57 publications
(137 reference statements)
1
27
0
1
Order By: Relevance
“…Thus, since a pregnant woman is a particular entity with a fetus in the uterus, SARS-CoV-2 infection affects not only the pregnant woman herself but also the fetus [30] . Second, SARS-CoV-2 infection in pregnant mothers can cause placental dysfunction, resulting in intrauterine hypoxia [31] . This infection can cause localized placental hypoxia through direct damage to the placental villi [32] .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, since a pregnant woman is a particular entity with a fetus in the uterus, SARS-CoV-2 infection affects not only the pregnant woman herself but also the fetus [30] . Second, SARS-CoV-2 infection in pregnant mothers can cause placental dysfunction, resulting in intrauterine hypoxia [31] . This infection can cause localized placental hypoxia through direct damage to the placental villi [32] .…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence supports coronavirus transmission by semen but not through vaginal fluids [ 38 ]. Congenital transmission of SARS-CoV-2 has been documented with clinical-pathological features [ 39 , 40 ]. Therefore, SARS-CoV-2 sexual and transplacental transmission may be considered in epidemiological studies.…”
Section: Discussionmentioning
confidence: 99%
“…Autopsy examination was performed in five cases that showed that all stillborns were anatomically normal with no microscopic evidence that SARS-CoV-2 had affected any fetal organ, and the authors ascribed the fetal deaths as due to placental insufficiency resulting from SARS-CoV-2 placentitis. In Sweden, Zaigham and colleagues reported five stillborn fetuses, including one set of twins, from mothers having COVID-19 infection [ 91 ]. The placentas of all stillborns were characterized by the findings of SARS-CoV-2 placentitis, and the authors concluded that the placental pathology-extensive fibrinoid deposits accompanied by villous necrosis characteristic of massive perivillous fibrin deposition accompanied by intervillositis accounted for the clinical outcomes of the stillborn fetuses.…”
Section: Covid-19 Infection and Stillbirthmentioning
confidence: 99%
“…Maternal viremia with SARS-CoV-2 has been described to occur in cases of SARS-CoV-2 placentitis and intrauterine fetal demise [ 97 ], and it is highly probable that reported cases of SARS-CoV-2 placentitis and stillbirth were the result of an episode of the virus circulating in the mothers’ bloodstream at some time during the pregnancy. In the 68 cases of stillbirth and early neonatal death from placental insufficiency arising from SARS-CoV-2 placentitis described by Schwartz et al [ 93 ], as well as the six perinatal deaths from Ireland described by Fitzgerald et al [ 78 ], the five stillborns from France reported by Debucs et al [ 92 ], five stillborns from Sweden reported by Zaigham et al [ 91 ], and others [ 98 ], the mothers were all unvaccinated for coronavirus.…”
Section: Potential Importance Of Vaccination Of Pregnant Women To Red...mentioning
confidence: 99%